DIGITAL JOURNALISM: multifaceted research in the development of didactics and production processes - Barcellos, Zanei (2021)
The internet is the main source of news for Brazilians, the smartphone is the preferred device to reach them and social media have overtaken television as the hegemonic journalistic medium. Fragmented journalism in cyberspace demands new narratives, new media formats, production and distribution processes. Algorithms and artificial intelligence (AI) systems already perform many tasks, the profession reshapes itself and the teaching of digital journalism needs to keep up with the transformations. This article proposes multifaceted applied research as a way to develop narratives, apparatuses, production management systems and didactics capable of keeping up with technological evolutions and train journalists capable of researching and working in mutant environments.